Istikhdām Wasīlah al-Kharīthah aż-Żihniyyah Bi Ṭarīqah at-Ta`allum at-Ta`āwunī Bi Uslūb Musābaqāt Tanāfus al-Farq (Team Game Tournament) Li Tarqiyah Qudrah aṭ-Ṭalabah `Alā Fahm al-Iḍāfah Wa aṣ-Ṣifah - Nurmarini Nurmarini; Moch. Fajarul Falah (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2021)
Mind Mapping can be discribed as a graphic designs that provide the key to assist brain abilities by utilizing most of the thinking skills using words, images and colors. The title of this research is Using Mind Mapping Media with Cooperative Learning Methods Through Inter-group Competitions to Improve Students' Understanding of Al-Idhafah and As-Sifah (Experimental Research at Babun Najah Modern Islamic Boarding School in Banda Aceh). The method used is the True Experiment and the population is all students of Madrasah Tsanawiyah in the Babun Najah Modern Islamic Boarding School with a total of 492 students. The method used to determine the sample is a Cluster Random Sample from a population. The selected sample was students of class XI-Mia 2 as the control group and class Mia 4 as the experimental group. This study has two objectives, to find out how students respond in the application of Mind Maps with Cooperative Learning Methods through Inter-Group Competitions to Improve Students' Understanding of Al-Idhafah and As-Sifah and their effectiveness. And the result of this research is the value of t-count is greater than t-table, which is 5.2> 2.05. And this shows the effectiveness of the application of mind map media with cooperative learning methods in teaching Al-Idhafah and As-sifah and has a good influence on second grade students of MadrasahTsanawiyah at the Babun Najah Modern Islamic Boarding School